Structural and electrical properties of chemically-doped barium zinc niobate perovskites - Kannan., Krishnakumaary (2020)
Ba(Zn1/3Nb2/3)O3 (BZN) perovskite has been recognised as an excellent dielectric material with moderately high dielectric constant (ε' = 25) and low dielectric loss, tan δ in the order of ~10-1 at ~30 °C. BZN perovskite has a space group of Pm3m and unit formula of (Z = 1). Ba2+ and O2- ions form a face-centred cubic unit cell whereas Zn2+ and Nb5+ ions occupy at the octahedral sites. In other words, Ba(B2+ 1/3B5+2/3)O3 has a combination of divalent and pentavalent cations with a ratio of 1:2 over the octahedral sites. In this work, an alkaline earth metal, Sr2+ and several transition metals, Ni2+, Cd2+ and Ta5+ were successfully introduced into the BZN perovskite through solid-state reaction. Several solid solutions were prepared successfully with the proposed chemical formulas, Ba(1-x)SrxZn1/3Nb2/3O3 (BSZN), BaZn(1/3-x)BxNb2/3O3 (B = Ni and Cd) (BZNN and BZCN) and BaZn1/3Nb(2/3-x)TaxO3 (BZNT), respectively. The solid solution limits of Sr-doped, Ni-doped, Cd-doped and Ta-doped BZN perovskites were determined to be 0 ≤ x ≤ 0.4, 0 ≤ x ≤ 0.333, 0 ≤ x ≤ 0.333 and 0 ≤ x ≤ 0.67, respectively. Interestingly, a complete substitutional solid solution range was found in the Cd-, Ni- and Ta-series. In this perspective, this could be due both isomorphous Nb5+ and Ta5+ have similar crystallochemical characteristics, e.g. similar charge and identical ionic radii (0.64 Å);therefore, these cations are interchangeable. Despite the relatively smaller ionic radii of Ni2+ (0.69 Å) and larger ionic radii of Cd2+ (0.95Å) than of Zn2+(0.74 Å), these two dopants could fully replace Zn2+ at the 6-coordinated site. This may due to the overall large unit cell formed by a Ba2+ is large enough to accommodate these substitutions. These doped BZN solid solutions crystallised in a cubic symmetry with their lattice parameters, a = b = c found to be in the range 4.0917(3)-4.1693(13) Å (Cd-series), 4.0917(3)-4.0786(6) Å (Ni-series), 4.0917(3)-4.0543(9) Å (Sr-series) and 4.0917(3)-4.1028(1) Å (Ta-series), respectively. The linear correlation between lattice parameter and composition also showed that the Vegard's Law was obeyed. Both TGA and DTA analyses confirmed that all these doped BZN perovskites are thermally stable as neither phase transition nor weight loss was discernible over the studied temperature range ~30-1000°C. Meanwhile, the functional groups of the samples were identified by using FTIR in the wavenumber range 250-1500 cm-1. Besides that, the randomly distributed polyhedral grains of surface morphologies of these samples exhibiting a broad distribution of mean grain sizes with increasing dopant concentrations. Moreover, all these doped perovskites exhibited relatively larger crystallite sizes, as calculated by Williamson-Hall method, than those values determined by Scherrer method. The negligible small internal strain values showed the absence of structural deformation within all the doped perovskites. The Arrhenius conductivity plots of all these doped perovskites showed linear and reversible characteristics in a heating-cooling cycle. The activation energies of BZCN, BZNN, BSZN and BZNT perovskites are found in the range 2.51-3.19 eV, 2.44-3.19 eV, 2.13-3.19 eV and 1.71-3.19 eV, respectively. All the BZN perovskites appeared to be highly insulating with moderate low ε' and low tan δ at ~30 °C. The recorded ε' values of Cd-, Ni-, Sr- and Ta-series are in the range 24-29, 13-25, 15-25 and 19-27 respectively, at ~30 ºC and 1 MHz. The recorded tan δ values of BZCN-, BZNN-, BSZN- and BZNT-series were determined to be in the range 0.24-0.38, 0.22-0.36, 0.25-0.31 and 0.29-0.61, respectively, at ~30 ºC and 1 MHz. In conclusion, BaZn1/3Nb2/3O3 and doped materials were successfully synthesised by solid-state reaction method at the optimised conditions. All these doped materials exhibited interesting insulating properties at low temperature regions that may be due to high resistivity of grain boundary. The structural and electrical properties of chemically-doped barium zinc niobate perovskite had been demonstrated to be highly dependent on the composition and crystal structure.